(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
Typically, the stratigraphic record of syn-eruptive fluvial successions is a pyroclastic-rich one. It includes an alternation of braided channel deposits and sheet-like floodplain strata, in which the occurrence of paleosols with in situ trees and primary pyroclastic deposits is common. The participation of facies formed from sediment-laden flows is also a conspicuous feature in these successions. Nevertheless, the disturbances occurred in the chilean Blanco River in 2008, as a consequence of the large tephra influx from the Chaitén Volcano eruption, result in discrepancies with the mentioned conceptual background including the plan-view form and filling of channels, and lateral compositional changes along the river. These discrepancies would response to local conditions such as precipitation, vegetation, topography, and type and amount of available sediment. Furthermore, the connection between the Blanco River and the Pacific Ocean, adds an additional feature to syn-eruptive fluvial successions, represented by associated delta plain deposits composed of volcaniclastic sands.